2018
DOI: 10.1021/acscatal.7b03639
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Carbon Deposits on the Cobalt-Catalyzed Fischer–Tropsch Reaction: Evidence of a Two-Site Reaction Model

Abstract: One of the well-known observations in the Fischer–Tropsch (FT) reaction is that the CH4 selectivity for cobalt catalysts is always higher than the value expected on the basis of the Anderson–Schulz–Flory (ASF) distribution. Depositing graphitic carbon on a cobalt catalyst strongly suppresses this non-ASF CH4, while the formation of higher hydrocarbons is much less affected. Carbon was laid down on the cobalt catalyst via the Boudouard reaction. We provide evidence that the amorphous carbon does not influence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
91
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(101 citation statements)
references
References 63 publications
10
91
0
Order By: Relevance
“…However, the fixed-bed reactor is subjected to local overheating of the catalyst surface that may lead to a fast deactivation and to high methane selectivity [309]. This behavior was clearly observed in FTS using fixed-bed reactors for carbon supported cobalt catalyst [312]. In this context, the development of novel FTS catalysts with high thermal conductivity for efficient heat transfer is a key challenge in FTS.…”
Section: Monolithic Structure For Carbon Supported Cobalt Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the fixed-bed reactor is subjected to local overheating of the catalyst surface that may lead to a fast deactivation and to high methane selectivity [309]. This behavior was clearly observed in FTS using fixed-bed reactors for carbon supported cobalt catalyst [312]. In this context, the development of novel FTS catalysts with high thermal conductivity for efficient heat transfer is a key challenge in FTS.…”
Section: Monolithic Structure For Carbon Supported Cobalt Catalystsmentioning
confidence: 99%
“…Since the FTS is a rather complex reaction, this approach does not account for the mechanisms of formation of different reaction products [41,59]. In order to overcome this problem, the new approaches consist in using microkinetics [65][66][67], DFT calculations [68,69], or to combine DFT calculations and microkinetics in order to elucidate the reaction mechanism [70]. Yang et al [70] combined DFT, transient, and steady-state kinetic modeling to elucidate the reaction mechanism in FTS using a 20%Co/CNTox catalyst to collect the experimental data.…”
mentioning
confidence: 99%
“…[17,18] Miao et al [19] reviewed possible mechanisms during CO and CO 2 methanation focusing mainly on Ni and Ru catalysts. Chen et al [20] reported that amorphous carbon formed on the cobalt surface during methanation can easily be removed under reaction conditions, whereas graphitic carbon is deposited irreversibly. Furthermore, they suggest that CO is more active in methanation than CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, carbon formation plays an important role. Chen et al [20] reported that amorphous carbon formed on the cobalt surface during methanation can easily be removed under reaction conditions, whereas graphitic carbon is deposited irreversibly. This inactive carbon is mainly located on the terrace sites of the cobalt and decreases the CH 4 selectivity because of blocking the favored sites for CH x hydrogenation.…”
Section: Introductionmentioning
confidence: 99%
“…Today, carbon-supported catalysts are receiving attention, especially in regard to their application in the production of synthetic automobile fuels through the Fischer–Tropsch synthesis (FTS) process [ 12 ]. Some authors have indicated that the presence of graphitic carbon in such catalysts seems to enhance the hydrocarbon chain-growth probability [ 13 ]. The methods used to prepare these FTS catalysts vary greatly, from incipient wetness impregnation [ 14 ] to micro-emulsion [ 15 ], sol-gel [ 16 ], or colloidal synthesis, coupled with the chemical reduction of the metal salts [ 17 ].…”
Section: Introductionmentioning
confidence: 99%